2022
DOI: 10.1186/s13054-022-03954-w
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the 2020 ERC/ESICM prognostication strategy algorithm after cardiac arrest

Abstract: Purpose To assess the performance of the post-cardiac arrest (CA) prognostication strategy algorithm recommended by the European Resuscitation Council (ERC) and the European Society of Intensive Care Medicine (ESICM) in 2020. Methods This was a retrospective analysis of the Korean Hypothermia Network Prospective Registry 1.0. Unconscious patients without confounders at day 4 (72–96 h) after return of spontaneous circulation (ROSC) were included. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
1
15
2
Order By: Relevance
“… 29 In a recent guideline validation study from South-Korea where therapy is rarely withdrawn, Youn et al reported a specificity of only 86% for the finding of a “poor CT” when evaluated by radiologists blinded to clinical data. 6 Similar results have been reported for diffusion-weighted sequences on MRI. 35 Although combinations of imaging techniques with other prognostic methods predicted poor outcome without false positive predictions in validation studies, the lack of a standardized radiological assessment of HIE may pose a risk for patients.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“… 29 In a recent guideline validation study from South-Korea where therapy is rarely withdrawn, Youn et al reported a specificity of only 86% for the finding of a “poor CT” when evaluated by radiologists blinded to clinical data. 6 Similar results have been reported for diffusion-weighted sequences on MRI. 35 Although combinations of imaging techniques with other prognostic methods predicted poor outcome without false positive predictions in validation studies, the lack of a standardized radiological assessment of HIE may pose a risk for patients.…”
Section: Discussionsupporting
confidence: 80%
“… 35 Although combinations of imaging techniques with other prognostic methods predicted poor outcome without false positive predictions in validation studies, the lack of a standardized radiological assessment of HIE may pose a risk for patients. 6 , 29 , 36 , 37 For this reason, since decisions on WLST within the TTM2 trial could also be based on CT findings, we will evaluate how well our radiological assessments correlate with blood levels of a surrogate marker of brain injury, the serum concentration of NFL. We have previously demonstrated that low levels of NFL predicted good outcome in 95% of patients, and that by combining biomarkers with other prognostic methods, the risk of false pathological CT evaluations could be minimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, it is important to achieve a FPR of zero because poor outcome predictors can be used to determine the WLST; but high sensitivity at FPR 0% is required to be useful as a predictive tool [33]. However, in the recently reported study, the external validation of the 2020 ERC/ESICM prognostic strategy algorithm after cardiac arrest, a FPR of 0% was achieved; but the sensitivity was at the level of 60% [34]. In this study, DW-MRI provided results within 6 h after ROSC, did not require specific expertise to discriminate P HSI only, and showed a sensitivity of 74.2% at FPR 0% to predict poor neurological outcome.…”
Section: Discussionmentioning
confidence: 96%
“…The prognosis was considered poor when there was one abnormal result for any single predictor (the absence of brainstem re exes, injury on brain CT or DWI, highly malignant EEG, high NSE level, and absence of the N20 wave on SSEP). We also used the multimodal algorithm recommended by the European Resuscitation Council/European Society of Intensive Care Medicine considering a combination of ≥ 2 abnormal results on any prognostic tests to indicate a poor outcome [15,21].…”
Section: Variablesmentioning
confidence: 99%